Knowledge is Not Related to Iron Tablets Consumption Compliance in Pregnant Women - Irma Darmawati; Dewi Marfuah; Leli Nurleli (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aim: In Indonesia, anaemia is one of the leading causes of maternal mortality. Inadequate iron (Fe) supplementation is one of the causes of anaemia in pregnant women. Researchers have found that what pregnant women know affects how they act when they take Fe tablets. Still, the most recent research shows that good knowledge is not always linked to taking Fe tablets in a good way. This study aims to determine the relationship between iron tablet compliance and the knowledge of pregnant women. Method: This study was a correlational study with a cross-sectional design in 2019. The sample in this study was 53 pregnant women obtained using the stratified proportional random sampling technique in Bandung. A questionnaire was used to collect data, and Spearman rank correlation was used to analyze the data. Result: The correlation test showed a significance level of 0.627 (value > 0.05), which means there is no correlation between pregnant women's knowledge about Fe tablets and compliance. Conclusion: A good understanding of pregnant women does not always correspond with women's observation of Fe tablet consumption. Other factors must be examined more closely. Pregnant women must be motivated and have good family support during their pregnancy.